Pan-India influenza-like illness (ILI) and Severe acute respiratory infection (SARI) surveillance: epidemiological, clinical and genomic analysis - Potdar, Varsha; Vijay, Neetu; Mukhopadhyay, Labanya; Aggarwal, Neeraj; Bhardwaj, Sumit Dutt; Choudhary, Manohar Lal; Gupta, Nivedita; Kaur, Harmanmeet; Narayan, Jitendra; Kumar, Prabhat; Singh, Harpreet; Abdulkader, Rizwan Suliankatchi; et al. (Frontiers in Public Health, 2023)
Abstract: Background: Over time COVID-19 testing has significantly declined across the world, however, it is critical to monitor the virus through surveillance. In late 2020, WHO released an interim guidance, advising use of existing GISRS (Global Influenza Surveillance and Response System) for integrated surveillance of Influenza and SARS-CoV-2. Methods: Since July 2021, we initiated pan-India integrated surveillance for Influenza and SARS-CoV-2 through the geographically representative network of Virus Research & Diagnostic Laboratories (VRDLs) across 26 hospital & laboratory sites and 70 community sites. A total of 34,260 Influenza Like Illness (ILI) and Severe Acute Respiratory Illness (SARI) cases were enrolled from 4th July 2021 - 31st October 2022. Findings: Influenza A(H3) alongwith type (B/Victoria) and A(H1N1)pdm09 predominated during 2021 and 2022 monsoon seasons respectively. SARS-CoV-2 Delta and Omicron 'Variant of Concern' (VoC) predominated in 2021 and 2022 respectively. Increased proportion of SARI was seen in extremes of age: 90% cases in <1 year; 68% in 1-<5 years and 61% in ≥80yrs age group. 40.7% of enrolled cases only partially fulfilled WHO ILI and SARI case definitions. Influenza and SARS-CoV-2 infected co-morbid patients had higher risk of hospitalization, ICU admission and oxygen requirement. Interpretation: Results depict varying strains and transmission dynamics of Influenza and SARS-CoV-2 viruses over time, thus emphasizing the need to continue and expand surveillance across countries for improved decision making. The study also describes important information related to clinical outcomes of ILI and SARI patients and highlights the need to review existing WHO ILI and SARI case definitions.